Study on autonomic dysfunction and metabolic syndrome in Chinese patients. Issue 6 (9th May 2016) - Zhu, Ling; Zhao, Xiaolan; Zeng, Ping; Zhu, Jianguo; Yang, Shuwen; Liu, Annan; Song, Yuehua
Abstract: Aims/Introduction: There is still a lack of simple methods and instruments for the early assessment of autonomic dysfunction in metabolic syndrome patients. Assessment of sudomotor function has been proposed to explore autonomic function, and could be used as an early biomarker for metabolic syndrome. In the present study, we use a quick and non‐invasive method to measure sudomotor function, and aimed to evaluate its efficacy to identify metabolic syndrome in a Chinese population. Materials and Methods: Information on the 1, 160 Chinese participants involved in the study, such as age, sex, blood pressure, waist circumference, body mass index, fasting plasma glucose and lipid profile, and SUDOSCAN, was recorded. During the sudomotor test, patients were asked to place their bare hands and feet on large electrodes. The test took 2 min to carry out, was painless and no participant preparation was required. Results: A total of 567 participants were diagnosed with metabolic syndrome. The prevalence of metabolic syndrome correlated significantly with increasing SUDOSCAN cardiac risk score ( P for trend <0.0001). Furthermore, an increase in cardiac risk score value was associated with an increase in the number of metabolic syndrome components ( P for trend <0.0001). Compared with the no‐risk group (cardiac risk score <20), participants in the high‐risk group (cardiac risk score ≥30) had a 2.83‐fold increased risk of prevalent metabolic syndrome ( P < 0.0001), and 1.51‐fold increased risk ( P = 0.01) after adjustments. Conclusions: Autonomic dysfunction is correlated to components of metabolic syndrome. The role of SUDOSCAN in the screening of at‐risk populations for metabolic syndrome has to be confirmed by further studies. Abstract : In this work, we evaluated the relationship of autonomic function with metabolic syndrome using a quick and non‐invasive method to measure sudomotor function.